Огнеупоры для промышленных агрегатов и топок: справочник в двух книгах - Кащеев И. Д. Иван Дмитриевич; Алфеева В. Г. Вера Григорьевна; Ладыгичев М. Г. Михаил Григорьевич; Нагинский М. З. Михаил Зиновьевич; Перепилицын В. А. Владимир Алексеевич; Речнева Л. А. Любовь Аркадьевна; Шатилов О. Ф. Олег Федорович (Москва, Интермет Инжиниринг, 2000)
Сост. указ. на обороте тит. л.